INFLUENCE OF LIGHT SPECTRUM AND NAPHTHALENE ACETIC ACID ON ROOTING OF SHOOTS FOR TWO VARIETIES OF GERBERA JAMESONII IN VITRO - & Hamad, AL-Hamidawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research was conducted at the plant tissue culture Lab. College of Agriclture, University of Baghdad from February to October 2015. The aim of the study was investigate the influence of light quality and Naphthalene Acetic Acid(NAA) on some properties of roots for two varieties Martinque and Yanara shoots of Gerbera jamesonii, cultured on MS medium supplemented with 0.3 mg.L -1 Spermidine. The results indicated that 1/2 MS medium with free auxin NAA gave the highest percentage of rooting (75 %) Which differed significantly from the other concentrations of NAA. White light gave the hightest percentage of rooting (89 %), that was not significantly different from the red light (78%) . While the treatment of Martinque variety under White light gave the highest percentage of rooting (100%), that was not significantly different from Yanara variety that gave (78%). MS medium with free auxin NAA gave the highest number of roots (7.5 % root/shoot ) that was significantly different on all the other concentrations of NAA. MS medium with free auxin NAA under White light of roots (6.6 root/shoot) at Martinque variety . While MS medium with free auxin NAA under blue light gave the highest number of roots (10.10 roots/shoot) that was not different significantly from red light it gave (8.9 root/shoot) Martinque variety gave the highest rate of root length ( 1.62 cm) Which not differend significantly from Yanara variety it gave (1.49 cm) While The treatment of Martinque variety under White light with NAA- free medium gave the highest rate of root length (3.40 cm) and was significantly different on all the other interactions